Observation of the Cumbre Vieja volcano plume above the Observatorio del Roque de los Muchachos with the Barcelona Raman LIDAR. Issue 1 (1st December 2022) - Živec, M; Ballester, O; Blanch, O; Boix, J; Calisse, P G; Campoy Ordaz, A; Doro, M; Font, L; Garcia, R; Gaug, M; Grau, R; Martinez, M; et al.
Abstract: The Cherenkov Telescope Array Observatory (CTAO), currently under construction, is the next-generation very-high-energy gamma-ray observatory, providing the coverage for photons in the energy range 20GeV to 300TeV. CTAO will increase detection sensitivity in the 100 GeV to 10TeV range by a factor of 5 — 10 with respect to present experiments. CTAO retrieves the properties of very-high-energy gamma-rays by measuring Cherenkov light emitted by atmospheric showers of secondary particles that incident gamma rays produce in upper layers of the atmosphere. The key for reaching the required energy measurement accuracy is a precise knowledge of the atmospheric transmittance for Cherenkov light, which can be obtained using a dedicated Raman LIDAR. The device should operate at 355nm (near the maximum of Cherenkov light spectrum) and have the capability of taking data at specific azimuth and zenith angles up to distances of 30 km, so that atmospheric transmission along all possible air-shower directions can be determined. The Barcelona Raman LIDAR (BRL) is the official CTAO Pathfinder prototype, developed for atmospheric characterization of the Northern CTAO Site at the Observatorio del Roque de los Muchachos (ORM) on the Canary island of La Palma. BRL was deployed at ORM for extensive on-field tests between February 2021 and May 2022. We report on the commissioning results, including the remote operation capabilities of the system and its contribution to the understanding of atmospheric phenomena during its deployment period. In particular, we report on the properties of the volcanic plume from the eruption of the Cumbre Vieja volcano on 22 September 2021.